Proceedings of the 6th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2017
DOI: 10.7712/120117.5705.18225
|View full text |Cite
|
Sign up to set email alerts
|

Collapse Capacity Prediction of Sdof Systems Equipped With Fluid Viscous Dampers

Abstract: There are various types of passive energy dissipation systems that are used in the seismic design of new structures and the seismic rehabilitation of existing structures. One of the most important kinds of passive energy dissipation systems, which reduce both displacements and accelerations simultaneously, are fluid viscous dampers (FVDs). Using FVDs can reduce the seismic response and improve the performance of structures during earthquake excitations and has a significant effect on the damping of structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…By using this type of modeling, it was possible to investigate the collapse capacity of structures, which requires computationally expensive Incremental Dynamic Analyses (IDAs). Gharyanpoor et al [16] evaluated the seismic collapse capacity of SDOF systems equipped with fluid viscous dampers considering the P-Delta effect. They concluded that the P-delta effect controls the collapse capacity of long-period SDOF systems.…”
Section: Introductionmentioning
confidence: 99%
“…By using this type of modeling, it was possible to investigate the collapse capacity of structures, which requires computationally expensive Incremental Dynamic Analyses (IDAs). Gharyanpoor et al [16] evaluated the seismic collapse capacity of SDOF systems equipped with fluid viscous dampers considering the P-Delta effect. They concluded that the P-delta effect controls the collapse capacity of long-period SDOF systems.…”
Section: Introductionmentioning
confidence: 99%